Effects of Oral Contraceptives Containing Desogestrel and Drospirenone on Clinical, Hormonal, and Metabolic Parameters of the Patients with Polycystic Ovary Syndrome: A Randomized Clinical Trial - Mina Amiri; Fahimeh Ramezani Tehrani; Razieh Bidhendi-Yarandi; Fatemeh Nahidi (مجله علمی دانشگاه علوم پزشکی کردستان, 2022)
Background and Aim: Despite the theoretical superiority of oral contraceptives (OCs) containing antiandrogenic progestins, to the products with androgenic activity, the clinical benefits of these compounds remain unknown. This study aimed to compare the efficacy of OCs containing desogestrel (DSG) or drospirenone (DRSP) on the hormonal, clinical and metabolic parameters of the patients with polycystic ovary syndrome (PCOS). Materials and Methods: This study was a randomized clinical trial and included 126 patients with PCOS. Patients were randomly assigned to one of the intervention groups using OCs containing DSG or DRSP. Outcomes of interest, including serum androgens, Ferriman-Gallwey score, and anthropometric and metabolic parameters were measured at the baseline, third, and sixth months of treatment. Results: After 3 to 6 months of treatment with OCs, we found no significant difference between the two groups in regard to serum androgen levels. There were also no significant differences between the two treatment groups, in terms of Ferriman-Gallwey score and anthropometric parameters, except for waist circumference in the sixth month of treatment (P = 0.011). After 3 months of the intervention, patients treated with OCs containing DSG had higher levels of low-density lipoprotein cholesterol (LDL) (P = 0.017), higher systolic (P = 0.013) and diastolic blood pressures (P = 0.008) than those treated with OCs containing DRSP. Conclusion: Although use of OCs containing antiandrogenic and androgenic progestins had the same effects on hormonal profiles, anthropometric and hirsutism parameters, compounds containing DSG were associated with more negative effects on serum lipids and blood pressure.